Más allá de la frontera nacional: la Federación Latinoamericana de Asociaciones de Familiares de Detenidos-Desaparecidos (FEDEFAM) y la memoria transnacional de la desaparición forzada en México - María Angélica Tamayo Plazas (Caravelle)
This paper analyses relations among FEDEDAM, Eureka Comitee and AFADEM during the 80s as a training space for memories of enforced disappearances. We examine from primary sources, some written some oral, the organisations’ trajectories and spots of memories’ production and circulation. We assert that within the common work concerning denunciation and search for justice, narrarives were made up as well as transnational memorial practices shared by parents’ organizations in Mexico and through the Latin American network issued by the federation.